Analisis Implementasi Kebijakan Pemberian Pengurangan Bea Perolehan Hak Atas Tanah Dan Bangunan Untuk Turun Waris Di Kota Bukittinggi - Razi, Fachrul; Khairul, Khairul (CV. ITTC INDONESIA, 2022)
This study aims to analyze the implementation of the policy of granting reductions, relief and exemption of fees for the acquisition of land and building rights for inheritance that has been carried out by the Bukittinggi City Government and other factors that contribute to the implementation of the policy of granting reductions, waivers and exemptions from fees for the acquisition of rights to land. Land and buildings are inherited. This type of research is qualitative research with a phenomenological approach. The results of the study found that the communication carried out by the implementor was a one-way communication, through intermediary village officials and land deed officials, not directly conveyed to the community, the resources owned by the implementor for staff in quantity were sufficient, but in quality there was still a shortage, the provision of adequate facilities and infrastructure, but still limited in terms of financial support. The implementor strongly supports the implementation of this policy in accordance with the SOP, but the time required to process a request is still too long. Other factors that contribute to the policy of granting reductions, waivers and exemptions for Inherited BPHTB are Land Value Zone Assessment and Changes in Tariffs and NPOPTKP specifically for Inherited BPHTB Keywords: Granting of Reduction of Duties on Acquisition of Inherited Land and Building Rights